Elementy współpracy polskich Wojsk Specjalnych i polskiego kontrwywiadu wojskowego w operacjach typu COIN. Casus Afganistanu - Machniak, Arkadiusz (Polityka i Społeczeństwo, 2021)
A COIN operation involves both insurgents and local people. Its main goal is to neutralize all conditions enabling the development of insurgent movements or conducive to their development. In COIN operations, the basic efficiency criterion is the destruction or significant reduction of the opponent’s effectiveness and its ability to use local people for its own purposes. Military counterintelligence is responsible for analyzing the capabilities and organizational structure of the enemy’s reconnaissance system, including terrorist organizations or rebels, and planning undertakings that neutralize enemy activities, achieved, among others by recognizing its capabilities and taking remedial action on this basis. Anti-partisan operations constitute a coordinated effort to combat guerrilla activities in the theatre of war of a varied military, paramilitary, political, economic, psychological, and social character, aimed against insurgents and against their impact on the state and the society.